Education in prison: a pedagogical challenge - Riolo, Giulia (Form@re - Open Journal per la formazione in rete, 2024)
This article offers a reflection on the role of education in prison, considering it first of all a human right, as stated by numerous national and international declarations. The different educational opportunities for detainees are explored, underlining the importance of integrating formal education with non-formal and informal education, in order to promote the transformative growth of the person. Reference is also made to some good practices developed in the Italian prison context. Finally, this work considers the critical issues and pedagogical challenges that must be addressed, so that educational experiences can contribute positively to the re-education of the detained person. L’educazione in carcere: una sfida pedagogica. Questo articolo offre una riflessione sul ruolo dell’educazione in ambito carcerario, considerandola prima di tutto un diritto umano, come affermato da numerose dichiarazioni nazionali e internazionali. Si esplorano le diverse opportunità educative per le persone detenute, sottolineando l’importanza di integrare l’educazione formale con quella non formale e informale, al fine di promuovere la crescita trasformativa della persona. Si fa riferimento anche ad alcune buone pratiche sviluppate nel contesto carcerario italiano. Infine, questo lavoro considera le criticità e le sfide pedagogiche che devono essere affrontate, affinché le esperienze formative possano contribuire positivamente alla rieducazione della persona detenuta.